2015
DOI: 10.4103/2230-8598.161523
|View full text |Cite
|
Sign up to set email alerts
|

Dengue epidemic management in a developing country

Abstract: Context: Dengue epidemic causes a wide spectrum of illness ranging from mild asymptomatic illness to severe fatal dengue. The cumulative dengue diseases burden has attained an unprecedented proportion in recent times with a sharp increase in the size of the human population at risk. Aims: Use of the WHO criteria (2012) for triage of dengue patients in an epidemic in a developing country with resource crunch of trained manpower and infrastructure. Settings and Design: The study was a retrospective and descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…22,26 Nair B et al reported 25% frank bleeding with epistaxis being most common. Melena and epistaxis were commonest bleeding manifestations noted which is similar to observation made in the study by Ahmed et al 23,27 In this study, children with bleeding tendencies were not necessarily those having low platelet count, indicating a combination of causes such as thrombocytopenia, coagulopathy, and vasculopathy leading to bleeding manifestations.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…22,26 Nair B et al reported 25% frank bleeding with epistaxis being most common. Melena and epistaxis were commonest bleeding manifestations noted which is similar to observation made in the study by Ahmed et al 23,27 In this study, children with bleeding tendencies were not necessarily those having low platelet count, indicating a combination of causes such as thrombocytopenia, coagulopathy, and vasculopathy leading to bleeding manifestations.…”
Section: Discussionsupporting
confidence: 89%
“…6.7% of cases had seizures which was similar to 6.8% seizures presentation noted by Nair B et al 23 As observed in the study done by Wang C et al arthralgia and myalgia were relatively less common complaints in children compared to adults whereas pain abdomen (32.5%) and vomiting (60.5%) constituted the more common presenting symptoms and were seen more commonly in severe dengue patients. 28 Various studies have reported that Indian children with DHF have a lower than expected rise in hematocrit during the plasma leakage period due to the high prevalence of iron deficiency anemia.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations